Akutes Koronarsyndrom in der Praxis – Was sollte der Hausarzt tun? - Stadler, Stefan; Endemann, Dierk; Maier, Lars S. (DMW - Deutsche Medizinische Wochenschrift, 2017)
Acute myocardial infarction is the second most common cause of mortality in Germany after chronic ischemic cardiac disease. It is essential to think of acute coronary syndrome also in patients who do not present with typical signs (pressure, tightness, pain, or a squeezing or aching sensation in the chest or arms that may spread to the neck, jaw or back) in the general practitioner’s practice. Vital signs (blood pressure, heart rate and oxygen saturation) must be measured; an ECG should be recorded and analyzed within ten minutes of first medical contact. The patient should be sedated, head and shoulders should be supported and an intravenous access should be established. Emergency medication that should be administered in practice is acetylsalicylic acid, an ADP receptor antagonist, morphine, nitrates, low molecular weight heparin and where necessary tranquilizers and oxygen (if peripheral saturation is below 90%). Monitored transport to the nearest clinic with percutaneous coronary intervention standby must be organized and this clinic must be informed about the arriving patient.
Keywords: akutes Koronarsyndrom; Praxis; Erstmaßnahmen